Vocal individuality of Sunda Scops-Owl (Otus lempiji) in Peninsular Malaysia - Yee, Siew Ann; Puan, Chong Leong; Chang, Phooi Kuan; Md Sharif, Badrul Azhar (Raptor Research Foundation, 2016)
Like many owl species, Sunda Scops-Owls (Otus lempiji) are difficult to monitor using traditional survey techniques, because of their nocturnal habits, secretive nature, and cryptic coloration. Individual variation in vocalizations could potentially be used to distinguish individuals of this owl species, as has been demonstrated for many bird species. The objectives of this study were to describe the territorial call of Sunda Scops-Owls, to determine whether the calls can be distinguished individually, and to examine whether the calls from the same individuals were stable over time. We analyzed 75 recordings collected from 12 owls from December 2014 to June 2015 in a lowland forest and oil palm smallholdings in Selangor State, Peninsular Malaysia. Using two temporal parameters and six frequency parameters derived from spectrogram, we employed ANOVA tests and found significant differences for all parameters among individual owls. Discriminant function analysis correctly classified 97.1% of the owl calls to the correct individuals. Based on the Wilcoxon signed-rank test, all vocal parameters did not vary significantly for the six birds that were vocally active over two predetermined survey sessions within the breeding period. Our results demonstrated that Sunda Scops-Owls can be identified individually by their vocalizations. This implies that assessing vocal individuality can be useful as a noninvasive method for surveying the Sunda Scops-Owls and the method should be further tested for other little-known owl species in the tropics.